Persistence of obligate intracellular pathogens: alternative strategies to overcome host-specific stresses - Riffaud, Camille M.; Rucks, Elizabeth A.; Ouellette, Scot P. (Frontiers in Cellular and Infection Microbiology, 2023)
In adapting to the intracellular niche, obligate intracellular bacteria usually undergo a reduction of genome size by eliminating genes not needed for intracellular survival. These losses can include, for example, genes involved in nutrient anabolic pathways or in stress response. Living inside a host cell offers a stable environment where intracellular bacteria can limit their exposure to extracellular effectors of the immune system and modulate or outright inhibit intracellular defense mechanisms. However, highlighting an area of vulnerability, these pathogens are dependent on the host cell for nutrients and are very sensitive to conditions that limit nutrient availability. Persistence is a common response shared by evolutionarily divergent bacteria to survive adverse conditions like nutrient deprivation. Development of persistence usually compromises successful antibiotic therapy of bacterial infections and is associated with chronic infections and long-term sequelae for the patients. During persistence, obligate intracellular pathogens are viable but not growing inside their host cell. They can survive for a long period of time such that, when the inducing stress is removed, reactivation of their growth cycles resumes. Given their reduced coding capacity, intracellular bacteria have adapted different response mechanisms. This review gives an overview of the strategies used by the obligate intracellular bacteria, where known, which, unlike model organisms such as E. coli, often lack toxin-antitoxin systems and the stringent response that have been linked to a persister phenotype and amino acid starvation states, respectively.